2016
DOI: 10.1016/j.mehy.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Why do premature newborn infants display elevated blood adenosine levels?

Abstract: Link to publicationCitation for published version (APA): Panfoli, I., Cassanello, M., Bruschettini, M., Colella, M., Cerone, R., Ravera, S., ... Ramenghi, L. (2016). Why do premature newborn infants display elevated blood adenosine levels ? Medical Hypotheses, 90, 53-56. DOI: 10.1016/j.mehy.2016 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…It is currently supposed that premature oxygen exposure contributes to the pathogenesis of the observed injuries . Our preliminary data showed that the blood of VLBW infants contains high levels of adenosine, as a function of body weight . The oxygen challenge may promote the observed adenosine increase.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…It is currently supposed that premature oxygen exposure contributes to the pathogenesis of the observed injuries . Our preliminary data showed that the blood of VLBW infants contains high levels of adenosine, as a function of body weight . The oxygen challenge may promote the observed adenosine increase.…”
Section: Introductionmentioning
confidence: 66%
“…As discussed previously, the presence in the exosome membranes of CD39 and CD73, two ecto‐enzymes that convert ATP to adenosine, may be the reason for missed detection of ATP . This would also justify the elevated blood adenosine content of the premature infants . Interestingly, MVs express P2Y1 and P2 × 1 purinergic receptors (see Supporting Information, Table 1).…”
Section: Discussionmentioning
confidence: 93%
“…Premature newborn infants display elevated levels of adenosine in the blood, and it has been claimed that this is because of blood-brain barrier immaturity. 97 P2X7 receptor suppression preserves blood-brain barrier integrity after intracerebral hemorrhage. 98 All subtypes of P1 adenosine receptors, A 1 , A 2A , A 2B , and A 3 , are expressed by vascular endothelium, A 2A and A 2B receptors being dominant.…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…The pathologies that we have studied may increase stress and fetal hypoxia and consequently, adenosine levels. In fact, the activity of adenosine is higher where oxygen demand is higher, such as in the retina (10,26).…”
Section: Discussionmentioning
confidence: 99%